2015
DOI: 10.1590/s1980-65742015000100009
|View full text |Cite
|
Sign up to set email alerts
|

The burden of abdominal obesity with physical inactivity on health expenditure in Brazil

Abstract: The purpose of this study was to analyze the association between the clustering of physical inactivity with abdominal obesity and public health care expenditure in Brazilian adults. The sample was composed of 963 patients of both genders, randomly selected in the Brazilian Public Health care System during 2010. Entire health care expenditures during the last year were computed and stratified into: medical consultations, medication dispensing, laboratory tests and overall expenditure. Waist circumference was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 25 publications
3
13
0
3
Order By: Relevance
“…It is well known that obesity increases the prevalence of chronic diseases and, subsequently, the demand for health services and its costs 42 . Recently, a study showed that obese and inactive individuals presented higher costs with medical consultations, use of medicines and total expenditures on healthcare when compared to individuals who did not have these variables associated 43 .…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that obesity increases the prevalence of chronic diseases and, subsequently, the demand for health services and its costs 42 . Recently, a study showed that obese and inactive individuals presented higher costs with medical consultations, use of medicines and total expenditures on healthcare when compared to individuals who did not have these variables associated 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed the prevalence of obesity according to BMI (WHO criteria) is 54% in women and 26% in men, which is nearly twice that of men. 16 Looking at the prevalence of abdominal obesity men have higher WHR compared to women. This shows that BMI is not the true indicator of obesity for people with diabetes or at risk for diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Os valores foram calculados e expressos em reais (R$). Esta metodologia tem sido utilizada em publicações prévias 5,21 .…”
Section: Procedimentosunclassified
“…Dentre as doenças que podem ser atenuadas e prevenidas com a prática frequente de exercícios físicos está a obesidade 3 que é considerada comorbidade importante, por estar relacionada ao desenvolvimento de outras doenças. Estudos anteriores têm reportado o significativo peso econômico da obesidade em sistemas de saúde ao redor do mundo 4,5 . Da mesma forma, dados científicos provenientes de pesquisa realizada no Sistema Único de Saúde (SUS) também demonstram que sujeitos com maior prática de atividades físicas apresentam menores gastos com saúde e ocorrência de obesidade 6 , informação importante visto que no Brasil, dados provenientes da Pesquisa Nacional de Saúde (PNS) realizada em 64 mil domicílios de 1.600 municípios de todo o país, entre agosto de 2013 e fevereiro de 2014 revelam que grande parte da população, 71,1%, é atendida pela rede pública de saúde, impactando em substanciais gastos 7 .…”
Section: Introductionunclassified